The Role of Non-Coding RNAs in Controlling Cell Cycle Related Proteins in Cancer Cells - Ghafouri-Fard, Soudeh; Shoorei, Hamed; Anamag, Farhad Tondro; Taheri, Mohammad (Frontiers in Oncology, 2020)
Cell cycle is regulated by a number of proteins namely cyclin-dependent kinases (CDKs) and their associated cyclins which bind with and activate CDKs in a phase specific manner. Additionally, several transcription factors (TFs) such as E2F and p53 and numerous signaling pathways regulate cell cycle progression. Recent studies have accentuated the role of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) in the regulation of cell cycle. Both lncRNAs and miRNAs interact with TFs participating in the regulation of cell cycle transition. Dysregulation of cell cycle regulatory miRNAs and lncRNAs results in human disorders particularly cancers. Understanding the role of lncRNAs, miRNAs and TFs in the regulation of cell cycle would pave the way for design of anticancer therapies which intervene with the cell cycle progression. In the current review, we describe the role of lncRNAs and miRNAs in the regulation of cell cycle and their association with human malignancies.